A Pedagogical Approach to Qur'anic Literacy: Implementing the Baghdadiyah Method for New Students at Darul Falah V Islamic Boarding School - Zuhria, Farida; Arini, Aida (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
This study aims to examine the implementation of the Baghdadiyah method in improving the Qur'an reading skills of new students at the Darul Falah V Islamic Boarding School in Cukir, Diwek, Jombang. The background of this study indicates that the Qur'an-reading skills of new students remain low, particularly in familiarity with the Hijaiyah alphabet, the articulation points of letters, reading fluency, and basic Tajwid. This study employed a descriptive qualitative approach using a case study design, incorporating observation, interviews, and documentation. The results indicate that the Baghdadiyah method was systematically implemented through the planning, implementation, and evaluation stages. During the planning stage, students were grouped by ability, teaching materials were developed, and lessons were prepared. The implementation stage was conducted in both group and individual settings using the